Macro Practice Supervision by Social Work Field Instructors. (3rd April 2022) - Castillo, Jason T.; Hendrix, Elizabeth W.; Nguyen, Van L.; Riquino, Michael R.
ABSTRACT: Although the Council on Social Work Education has identified field education and macro practice as core domains in social work education, there has been limited research examining the implementation of macro practice elements in field education settings. As part of a larger research project examining field instructors' inclusion of macro and diversity-based content in the field practicum placement, this exploratory study focused on (a) field instructors' integration of macro practice elements into the field practicum setting and (b) the amount of time field instructors allotted to discussing macro practice elements in their weekly supervision with students. Surveys were completed by 102 field instructors associated with an accredited undergraduate and graduate-level social work education program at a public university in the intermountain west region of the United States. This study found that field instructors integrate few or limited macro practice elements into the field practicum placement, field instructors spend minimal time discussing macro practice elements with students during weekly supervision, and the macro practice elements discussed varied across field instructors and differed among primary areas of practice focus in practicum settings. Implications for social work education and field practicum education are provided, and recommendations for future research are discussed.